Chemotherapy-Induced Regression of an Adrenocorticotropin-Secreting Pituitary Carcinoma Accompanied by Secondary Adrenal Insufficiency - Robert Frank Cornell; Daniel F. Kelly; Gal Bordo; Ty B. Carroll; Huy T. Duong; Julie Kim; Yuki Takasumi; James P. Thomas; Yee Lan Wong; James W. Findling (Case Reports in Endocrinology)
Purpose. Adrenocorticotropin- (ACTH-) secreting pituitary carcinomas are rare and require multimodality treatment. The aim of this study was to report the response to various therapies and discuss the potential development of secondary adrenal insufficiency with cytotoxic chemotherapy. Methods. This report describes a man with a large silent corticotroph adenoma progressing to endogenous hypercortisolism and metastatic ACTH-secreting pituitary carcinoma over a period of 14 years. Results. Seven years after initial presentation, progressive tumor enlargement associated with the development of hypercortisolism mandated multiple pituitary tumor debulking procedures and radiotherapy. Testing of the Ki-67 proliferation index was markedly high and he developed a hepatic metastasis. Combination therapy with cisplatin and etoposide resulted in a substantial reduction in tumor size, near-complete regression of his liver metastasis, and dramatic decrease in ACTH secretion. This unexpectedly resulted in symptomatic secondary adrenal insufficiency. Conclusions. This is the first reported case of secondary adrenal insufficiency after use of cytotoxic chemotherapy for metastatic ACTH-secreting pituitary carcinoma. High proliferative indices may be predictive of dramatic responses to chemotherapy. Given the potential for such responses, the development of secondary adrenal insufficiency may occur and patients should be monitored accordingly.